2018
DOI: 10.3233/jad-171150
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Obesity/Type 2 Diabetes and Lower Levels of Lithium in Rural Texas Counties May Explain Greater Alzheimer’s Disease Risk

Abstract: AD mortality rates are higher in rural counties when compared to urban counties, and this may be linked to greater physical inactivity, obesity, and diabetes, as well as lower trace lithium levels in tap water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Indeed, external risk factors including smoking, hypertension, depression, insulin resistance, diabetes, and obesity have been shown to account for ≈50% of all reported cases when combined [ 1 ]. Even improper sleep has been linked to increased risk of AD [ 9 , 10 ]. Many of these risk factors, such as T2D and obesity, contribute to what is described as metabolic dysregulation [ 11 , 12 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Indeed, external risk factors including smoking, hypertension, depression, insulin resistance, diabetes, and obesity have been shown to account for ≈50% of all reported cases when combined [ 1 ]. Even improper sleep has been linked to increased risk of AD [ 9 , 10 ]. Many of these risk factors, such as T2D and obesity, contribute to what is described as metabolic dysregulation [ 11 , 12 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Fatty acids are categorized into saturated fatty acids (SFA) and unsaturated fatty acids, which can be further grouped into mono-(MUFA) and polyunsaturated (PUFA) fatty acids. High intake of SFA is not only related to an increased risk of metabolic disorders like type 2 diabetes mellitus (T2DM), but also AD (Baranowski et al 2018b;de la Monte and Wands 2008;Profenno et al 2010). For example, cross-sectional (Kalmijn et al 2004) and longitudinal population-based studies have found positive correlations between increased SFA intake and a higher risk of mild cognitive impairment (MCI) and AD (Kalmijn et al 1997;Morris et al 2003).…”
Section: Western Dietmentioning
confidence: 99%
“…Regular exercise is another lifestyle factor that not only combats obesity and related metabolic diseases but also reduces the risk of AD (de Bruijn et al 2013;Ogino et al 2019). Epidemiological studies highlight positive correlations between physical inactivity and AD mortality rates (Baranowski et al 2018b;Laurin et al 2001). In agreement with these findings, a systematic review examining the role of physical activity as a potential preventative intervention for AD confirmed that there is an inverse association between physical activity and the risk of AD.…”
Section: Exercise and Admentioning
confidence: 99%
“…Clinical and epidemiological evidence highlights the fact that lifestyle factors, such as diet and exercise, are crucial in reducing the risk of late onset Alzheimer’s disease ( de la Monte and Wands, 2008 ; Pasinetti and Eberstein, 2008 ; Vagelatos and Eslick, 2013 ; Baranowski et al, 2018b , 2020 ). The accumulation of amyloid beta (Aβ) plaques is a pathological hallmark of Alzheimer’s disease ( Behl and Holsboer, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have identified physical inactivity and obesity as significant risk factors for Alzheimer’s disease mortality rates and disease progression ( Profenno et al, 2010 ; Baranowski et al, 2018b ). In humans, there appears to be a relationship between obesity and circulating plasma Aβ ( Mayeux et al, 2003 ; Balakrishnan et al, 2005 ; Luciano et al, 2015 ), along with evidence to support that higher levels of plasma Aβ can be used to predict the risk of developing Alzheimer’s disease and cognitive impairments ( Ida et al, 1996 ; Mayeux et al, 2003 ; Mayeux and Schupf, 2011 ).…”
Section: Introductionmentioning
confidence: 99%